Manajemen Pondok Pesantren dalam Membimbing Penyesuaian Diri Santriwati Baru di Pondok Pesantren Al- Amanah, Liabuku, Bau-bau, Sulawesi Tenggara. - Salsabila; Danial; Shaleh, Muhammad; Trisnawati, Ira (AL-MUNAZZAM : Jurnal Pemikiran dan Penelitian Manajemen Dakwah, 2025)
This research aims to determine (1) the general overview of self-adjustment among new female students (santriwati) at Al-Amanah Islamic boarding school, Liabuku, Bau-Bau, Southeast Sulawesi. (2) the management of the Islamic boarding school in guiding the self-adjustment of new female students at the modern Al-Amanah Islamic boarding school, Liabuku, Bau-Bau, Southeast Sulawesi. (3) To analyze the impact of Islamic boarding school management in guiding the self-adjustment of new female students at the modern Al-Amanah boarding school, Liabuku, Bau-Bau, Southeast Sulawesi. This research uses qualitative research methods with field research as the type of study. Data collection techniques were conducted through observation, interviews, and documentation, with data then analyzed using reduction techniques, data presentation, and conclusion drawing. The results of this research show that the general overview of self-adjustment among new female students at Al-Amanah Islamic boarding school includes five aspects of self-adjustment experienced by new female students: adjustment to environmental changes, stricter regulations, emotional adjustment, social aspects, and academic aspects. Al-Amanah Islamic boarding school guides the self-adjustment of new female students by preparing the Khutbatul Arsy Program while implementing management functions and elements. The impacts of this program are social, affective, and cognitive impacts.